Analysis of Service Quality to Increase Customer Satisfaction at Alfamidi Super on Jl. Medang Lestari, Gading Serpong - Putri, Christin; Fanani, Yusfita Dyah; Wirawan , Maryani (Yayasan Gema Bina Nusantara, 2023)
The purpose of this study is to measure the level of service that has been provided by the minimarket to consumers. In this study, the sample used was students, totaling approximately 34 respondents. This study used primary data because primary data was obtained through distributing questionnaires to students. Data analysis uses gap 5. In Quadrant 1 which shows high importance low performance is an element that needs to be considered because in the eyes of consumers this element is an important thing, in quadrant 2 which shows high importance high performance where performance and importance are owned in perception the consumer has been fulfilled well so that this element needs to be maintained, in quadrant 3 which shows low importance low performance where the performance of a company is not good but in the eyes of consumers it is not so important that it needs to be considered but not a priority for the company, and the last one in the quadrant 4 which shows low importance, high importance is something that is seen by consumers as not important, but in terms of the company's performance has been done well so as not to create low quality.